Exploring subtle features of yield surfaces of porous, ductile solids through unit cell simulations. (December 2020) - Chouksey, Mayank; Keralavarma, Shyam M.; Basu, Sumit
Abstract: A general computational technique for deriving macro yield surfaces from unit cells with a given microstructure has been proposed in a companion paper ( Chouksey, M., Keralavarma, S. M., Basu, S., 2019, "Computational investigation into the role of localization on yield of a porous ductile solid, " Journal of the Mechanics and Physics of Solids, 130, pp. 141–164 ). Using this technique, macro yield surfaces for porous ductile solids, represented by cuboidal unit cells containing ellipsoidal voids, have been generated and compared with suitable analytical yield criteria. These yield surfaces exhibit vertex-like features when the principal directions of the macro stress coincides with the axes of the ellipsoidal void. In this work, we study the effects of void spacing and orientation with respect to the principal directions n α ( α ∈ [ 1, 3 ] ) of the macro stress. Subtle changes in the yield surface are revealed when its traces are plotted on octahedral or meridional section planes in stress space. Further, the possibility of utilizing the computational framework to automatically generate complete macro yield surfaces by sampling the entire macro stress space, for a given microstructure, is demonstrated with examples where the space of applied macro stress states are limited by suitable assumptions. Highlights: Effect of void spacing and macro shear stresses on the macro yield of porous ductile solids has been explored. For prolate voids, void spacing affects the yielding only at higher triaxiality. For oblate voids, yielding is almost insensitive to void spacing. Yielding always happens by localization when the void axes and principal directions of macro stress do not coincide. Shear macro stresses tend to smoothen the yield loci.